Advancing Forest Management through Collaboration between Government and Local Communities: Case Study in West Bali KPH - Jun Ichihara (International Conference on Multidisciplinary Research Perspective, 2025)
Indonesia’s social forestry program and the establishment of Forest Management Units (Kesatuan Pengelolaan Hutan, KPH) aim to enhance sustainable forest management (SFM) through decentralized governance and community participation. This study analyzes forest management practices in the West Bali Forest Management Unit (KPH Bali Barat), focusing on Pulukan and Pendem villages in Jembrana Regency, where community forest management rights have been granted since 2017–2018. Using qualitative methods—including interviews with local leaders, social forestry groups, customary (adat) authorities, KPH officials, and other stakeholders, as well as site observations conducted from August 2024 to April 2025—the research examines institutional arrangements, socio-economic conditions, and cultural contexts shaping forest governance. Findings show that agroforestry development, ecotourism initiatives, and multi-stakeholder collaboration contribute to livelihood improvement and conservation outcomes, supported by the Balinese Hindu philosophy of Tri Hita Karana, which sacralizes forest spaces and reinforces community stewardship. However, limited financial resources, legal and managerial capacity gaps, and constraints on KPH authority hinder long-term sustainability. The study highlights the need for flexible governance that harmonizes cultural norms with formal regulations, strengthens KPH’s intermediary role, builds community capabilities across the value chain, and expands sustainable financing mechanisms. These insights contribute to understanding how cultural values, institutional frameworks, and collaborative governance interact in advancing SFM within Indonesia’s social forestry system